Radiomics integration into a picture archiving and communication system - Ivan Zhovannik; Suraj Pai; Talia A. da Silva Santos; Lars L.G. van Driel; Andre Dekker; Rianne Fijten; Alberto Traverso; Johan Bussink; René Monshouwer (Physics and Imaging in Radiation Oncology, 2021)
Radiomics is referred to as quantitative imaging of biomarkers used for clinical outcome prognosis or tumor characterization. In order to bridge radiomics and its clinical application, we aimed to build an integrated solution of radiomics extraction with an open-source Picture Archiving and Communication System (PACS). The integrated SQLite4Radiomics software was tested in three different imaging modalities and its performance was benchmarked in lung cancer open datasets RIDER and MMD with median extraction time of 10.7 (percentiles 25–75: 8.9–18.7) seconds per ROI in three different configurations.